Feasibility study for a full-service independent hotel: a case study in hotel x Bandung, Indonesia - Pudin Saepudin; Fajar Kusnadi Kusumah Putra; I Gusti Agung Wahyu Adrian (Journal of Economics, Business, and Accountancy Ventura, 2019)
The purpose of this study was to show the implementation of feasibility study for the hotel project by using Political, Economic, Social, and Technological (PEST) analysis, Porter’s five forces and Resource-Based View (RBV). A case study was conducted in a full-service independent four-star hotel project in Bandung, Indonesia. This study used a direct observation from the researchers in the hotel project and secondary data analysis from related documents to support the investigation. Finally, It also used capital budget calculation for recommendation for the feasibility of the hotel project. It showed that apparently the hotel X investment is feasible to proceed. Some recommendations are given for hotel owners related to the business environment analysis and in creating a feasibility study specifically design for the hotel business. Managerial implication of this study can be useful for companies in making the right decisions in the development or expansion, and to minimize the long-term losses. Limitation of this research is in only analyzing one hotel in a four-star classification; further analysis can be applied in different location, classification, and different types of hotel service.